A young female with pulmonary sarcoidosis masquerading as bronchial asthma (BIRDEM Medical Journal, 2026)
Sarcoidosis is a multisystem granulomatous disorder that commonly affects the lungs. Accumulation of nonnecrotizing granulomas and subsequently fibrosis in the lungs and other organs accounts for the clinical manifestations. A young female patient complaining of shortness of breath, cough and wheezing. First she was treated as asthma for long time and there was no improvement. Then a computed tomography of chest was performed and fine needle aspiration from hilar lymphnode confirmed pulmonary sarcoidosis. She received corticosteroid therapy for six months and her health situation become well.BIRDEM Med J 2026; 16(1): 33-35